Current Challenges in the Regulation of CO2 Emission of Road Vehicles - Kocsis, Dénes; Bellér, Gábor; T. Kiss, Judit; Árpád , István (International Journal of Engineering and Management Sciences, 2020)
Today, as part of the fight against climate change, regulations on greenhouse gas emissions are gaining significantly higher attention. Our work focuses on the European Union legislation on carbon dioxide emissions from road vehicles, with special emphasis on the target values. Current changes in CO2 measurement methods, as important issues of the regulations, are also reviewed within this article.